Asphalt Mixture

By adding a composite of new asphalt and specific polymer metal salts and regenerated asphalt aggregates to the asphalt mixture, the problem of the degradation of the performance of regenerated asphalt aggregates after long-term use is solved, and a high durability and flexible asphalt pavement effect is achieved.

JP7629069B2Active Publication Date: 2025-02-12KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023179697
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-10-18
Filing Date
2023-10-18
Publication Date
2025-02-12
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

In the prior art, the asphalt mixture made of regenerated asphalt aggregates decreases physical properties after long-term thermal history and ultraviolet exposure, resulting in insufficient hardness and flexibility, making it difficult to achieve a balance of durability and flexibility.

Method used

A mixture containing new asphalt, specific polymer metal salts and regenerated asphalt aggregates is used to form a composite by mixing under heating conditions to improve the dispersion of regenerated asphalt aggregates in new asphalt and improve the durability and flexibility of asphalt pavement.

Benefits of technology

It provides asphalt pavement with excellent paving performance, exhibiting high durability and low deformation characteristics, while improving resistance to rut and cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629069000001
    Figure 0007629069000001
  • Figure 0007629069000002
    Figure 0007629069000002
  • Figure 0007629069000003
    Figure 0007629069000003
Patent Text Reader

Abstract

To provide an asphalt mixture that uses recycled asphalt aggregate and provides asphalt pavement with superior physical properties such as durability and flexibility.SOLUTION: The present invention relates to an asphalt mixture containing new asphalt, the following polymer metal salt (P), and recycled asphalt aggregates. Polymer-metal salt (P): a metal salt of a polymer having a structural unit derived from an aromatic monomer and having an acidic group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an asphalt mixture, a method for producing the same, and a method for paving roads. [Background technology]

[0002] Asphalt pavement, which uses asphalt mixture, is used for paving roads, parking lots, freight yards, sidewalks, etc., because it is relatively easy to lay and the time from the start of paving work to the start of traffic is short. Asphalt pavement has a road surface formed from an asphalt mixture in which aggregate is bound with asphalt, the paved road has good hardness and durability.

[0003] Furthermore, in light of the recent rise in crude oil prices and the trend toward carbon neutrality, there is a demand for crushing waste asphalt pavement materials and using them as part of new aggregate in paving construction work. For example, Patent Document 1 discloses a recycled asphalt mixture obtained by mixing recycled asphalt aggregate cured with a recycling additive and / or a workability improving agent with new aggregate and new asphalt. The recycling additive includes a petroleum lubricant, and the workability improving agent includes a fatty acid compound and a glycol ether compound. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-37798 A Summary of the Invention [Problem to be solved by the invention]

[0005] Asphalt derived from recycled asphalt aggregate has deteriorated significantly due to long-term heat history and exposure to ultraviolet rays, so asphalt compositions using recycled asphalt aggregate have the problem of poor physical properties when paved due to the effects of the deteriorated asphalt. The technology described in Patent Document 1 requires that a recycling additive and / or a workability improving agent be added to recycled asphalt aggregate in advance, followed by curing. The present invention relates to an asphalt mixture using recycled asphalt aggregate that can provide an asphalt pavement having excellent pavement properties such as durability and flexibility, which are difficult to achieve in combination, a method for producing the asphalt mixture, and a road paving method. [Means for solving the problem]

[0006] The present invention relates to the following [1] to [3]. [1] Asphalt mixture containing new asphalt, the following polymer metal salt (P), and recycled asphalt aggregate. Polymer metal salt (P): A metal salt of a polymer having a structural unit derived from an aromatic monomer and having an acidic group. [2] A method for producing an asphalt mixture, comprising a step of mixing a new asphalt, the polymer metal salt (P) described below, and recycled asphalt aggregate under heated conditions. Polymer metal salt (P): A metal salt of a polymer having a structural unit derived from an aromatic monomer and having an acidic group. [3] A road paving method comprising a step of applying the asphalt mixture described in [1] above to a road to form an asphalt pavement layer. Effect of the Invention

[0007] According to the present invention, it is possible to provide an asphalt mixture which uses recycled asphalt aggregate and which can provide an asphalt pavement which has excellent pavement properties such as durability and flexibility, a method for producing the same, and a road paving method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Asphalt mixture] The asphalt mixture of the present invention contains a new asphalt, the polymer metal salt (P) described below, and recycled asphalt aggregate. Polymer metal salt (P): A metal salt of a polymer having a structural unit derived from an aromatic monomer and having an acidic group. The asphalt mixture of the present invention may be a mixture of a novel asphalt, a polymer metal salt (P), and an asphalt recycled aggregate.

[0009] The inventors have discovered that an asphalt mixture containing a new asphalt, a specific polymer metal salt, and recycled asphalt aggregate can provide an asphalt pavement with excellent pavement properties such as durability and flexibility, even if the asphalt mixture contains recycled asphalt aggregate. Hereinafter, when the term "pavement physical properties" is used simply in this specification, it means pavement physical properties such as durability and flexibility. The durability of asphalt pavement can be evaluated, for example, by the Marshall stability value. The flexibility of asphalt pavement can be evaluated, for example, by the flow value in the Marshall stability test. Asphalt pavement with excellent durability has, for example, excellent rutting resistance, and asphalt pavement with excellent flexibility has, for example, excellent crack resistance.

[0010] Although the detailed mechanism by which the effects of the present invention are obtained is unclear, part of it is thought to be as follows. The polymer metal salt of the present invention adsorbs with asphaltene in deteriorated asphalt derived from asphalt recycled aggregate due to nn interaction and affinity due to structure, forming a complex of asphaltene and polymer. And, since the acid anion groups of the ionized polymer repel each other in the complex of asphaltene and polymer, it is considered that the dispersibility in asphalt of the recycled aggregate to which the deteriorated asphalt is attached is improved, and an asphalt pavement with excellent physical properties such as durability and flexibility can be provided. That is, it is presumed that the polymer metal salt does not reduce the viscosity of the deteriorated asphalt, but improves the dispersibility in new asphalt of the recycled aggregate to which the deteriorated asphalt is attached.

[0011] <New asphalt> New asphalt is also called virgin asphalt or unused asphalt, and refers to asphalt that has never been used in asphalt pavement. As the new asphalt, various asphalts can be used as long as they have no history of use in asphalt pavement. For example, in addition to straight asphalt, which is petroleum asphalt for paving, modified asphalt can be mentioned. Modified asphalt can be blown asphalt; polymer modified asphalt modified with polymeric materials such as thermoplastic elastomers and thermoplastic resins. Straight asphalt is a residual bituminous material obtained by subjecting crude oil to atmospheric distillation equipment, vacuum distillation equipment, etc. Blown asphalt means asphalt obtained by heating a mixture of straight asphalt and heavy oil, and then blowing air into it to oxidize it. The asphalt is preferably selected from straight asphalt and polymer modified asphalt, and from the viewpoint of durability of asphalt pavement, polymer modified asphalt is more preferable, and from the viewpoint of versatility, straight asphalt is more preferable. As the polymer modified asphalt, asphalt modified with thermoplastic elastomer is more preferable. The modified asphalt is preferably a polymer modified asphalt, more preferably a polymer modified asphalt modified with a thermoplastic elastomer.

[0012] (Thermoplastic elastomer) Examples of the thermoplastic elastomer in the polymer modified asphalt modified with a thermoplastic elastomer include styrene / butadiene block copolymers, styrene / butadiene / styrene block copolymers, styrene / butadiene random copolymers, styrene / isoprene block copolymers, styrene / isoprene / styrene block copolymers, styrene / isoprene random copolymers, ethylene / vinyl acetate copolymers, ethylene / acrylic acid ester copolymers, styrene / ethylene / butylene / styrene copolymers, styrene / ethylene / propylene / styrene copolymers, polyurethane-based thermoplastic elastomers, polyolefin-based thermoplastic elastomers, isobutylene / isoprene copolymers, polyisoprene, polychloroprene, synthetic rubbers other than those mentioned above, and at least one selected from natural rubber. The thermoplastic elastomer in the modified asphalt is preferably at least one selected from styrene / butadiene block copolymers, styrene / butadiene / styrene block copolymers, styrene / butadiene random copolymers, styrene / isoprene block copolymers, styrene / isoprene / styrene block copolymers, styrene / isoprene random copolymers, ethylene / vinyl acetate copolymers, and ethylene / acrylic acid ester copolymers. Among these, from the viewpoint of durability of asphalt pavement, the thermoplastic elastomer is preferably at least one selected from styrene / butadiene block copolymer, styrene / butadiene / styrene block copolymer, styrene / butadiene random copolymer, styrene / isoprene block copolymer, styrene / isoprene / styrene block copolymer, styrene / isoprene random copolymer and ethylene / acrylic acid ester copolymer, more preferably at least one selected from styrene / butadiene block copolymer, styrene / butadiene / styrene block copolymer, styrene / butadiene random copolymer, styrene / isoprene block copolymer and styrene / isoprene random copolymer, even more preferably at least one selected from styrene / butadiene random copolymer and styrene / butadiene / styrene block copolymer. From the viewpoint of durability and surface appearance of the asphalt pavement, the content of thermoplastic elastomer in the polymer modified asphalt is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, and preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 10 mass% or less.

[0013] <Polymer metal salt (P)> The asphalt composition of the present invention contains the following polymer metal salt (P). Polymer metal salt (P): A metal salt of a polymer having a structural unit derived from an aromatic monomer and having an acidic group. The term "polymer metal salt (P)" encompasses embodiments in which the asphalt mixture contains ionized polymer-derived anions and metal cations.

[0014] The polymer portion of the polymer metal salt (P) has constitutional units derived from an aromatic monomer and has an acidic group. The aromatic monomer may have an aromatic skeleton in the main chain or in a side chain, but from the viewpoint of affinity with asphaltene, it preferably has an aromatic skeleton in the main chain. Examples of the aromatic ring skeleton include a benzene skeleton, a naphthalene skeleton, an anthracene skeleton, a tetracene skeleton, a pentacene skeleton, a triphenylene skeleton, and a pyrene skeleton, from the viewpoint of compatibility with asphaltene. Among these, from the viewpoints of availability and performance, a naphthalene skeleton and a benzene skeleton are preferred, and a naphthalene skeleton is more preferred. The aromatic ring skeleton may have a substituent. Examples of the substituent include alkyl groups such as methyl, ethyl, and butyl groups, and among them, from the viewpoint of ensuring compatibility with asphaltene, a methyl or ethyl group is preferred. The number of the substituents is preferably 1 to 3, more preferably 1. The acidic group of the polymer is present in a structural unit derived from an aromatic monomer in the polymer or in another portion thereof. Preferably, the structural unit derived from an aromatic monomer has the acidic group. The acidic group includes a sulfonic acid group and a carboxylic acid group, and is preferably a sulfonic acid group.

[0015] Examples of the polymer portion of the polymer metal salt (P) include those obtained by chain polymerization methods, particularly radical polymerization methods, those obtained by addition polymerization methods, those obtained by sequential polymerization methods, particularly condensation polymerization methods, those obtained by ring-opening polymerization methods, those obtained by living polymerization methods, those obtained by aromatic nucleophilic substitution reaction methods (also called aromatic electrophilic substitution reaction methods), and other polyphenylene sulfides, etc., and among these, those obtained by addition polymerization methods or condensation polymerization methods are preferred, and those obtained by condensation polymerization methods are more preferred.

[0016] An example of a polymer obtained by addition polymerization is polystyrene sulfonic acid having a structural unit derived from a styrene sulfonate salt.

[0017] Polymers obtained by condensation polymerization include aromatic sulfonic acid formalin condensates. Aromatic sulfonic acid formalin condensates are condensates of aromatic sulfonic acid and formaldehyde, and examples of the aromatic sulfonic acid include monocyclic aromatic sulfonic acids such as cresol sulfonic acid and phenol sulfonic acid; alkyl naphthalene sulfonic acids such as α-naphthalene sulfonic acid, β-naphthalene sulfonic acid, α-naphthol sulfonic acid, β-naphthol sulfonic acid, methyl naphthalene sulfonic acid, and butyl naphthalene sulfonic acid; polycyclic aromatic sulfonic acids such as creosote oil sulfonic acid; and lignin sulfonic acid. Among these, preferred are methyl naphthalene sulfonic acid formalin condensates, butyl naphthalene sulfonic acid formalin condensates, α-naphthalene sulfonic acid, and β-naphthalene sulfonic acid.

[0018] The polymer metal salt (P) is a base salt of the above polymer, preferably a sodium salt, potassium salt, or calcium salt, more preferably a sodium salt.

[0019] The weight average molecular weight of the polymer metal salt (P) is preferably 1,000 or more, more preferably 2,000 or more, even more preferably 2,500 or more, and preferably 100,000 or less, more preferably 75,000 or less, even more preferably 50,000 or less, and even more preferably 20,000 or less.

[0020] Examples of the polymer metal salt (P) include metal salts of aromatic sulfonic acid-formalin condensates such as methylnaphthalenesulfonic acid-formalin condensate sodium salt, butylnaphthalenesulfonic acid-formalin condensate sodium salt, α-naphthalenesulfonic acid, and β-naphthalenesulfonic acid; and examples of the metal salts of polymers having an aromatic skeleton in the side chain include metal salts of polystyrenesulfonic acid such as polystyrenesulfonate sodium salt.

[0021] Commercially available polymer metal salts (P) include "DEMOL MS", "DEMOL SN-B", "DEMOL N", "Mighty 100" and the like (all trade names) manufactured by Kao Corporation.

[0022] [Recycled asphalt aggregate] The asphalt mixture of the present invention contains recycled asphalt aggregate as an aggregate. Recycled asphalt aggregate is made by collecting used asphalt pavement, crushing it, and classifying it. The used asphalt pavement from which the recycled asphalt aggregate is derived contains asphalt and aggregate, and may contain other additives as needed.

[0023] The physical and chemical properties of the asphalt contained in recycled asphalt aggregate are deteriorated compared to new asphalt due to the influence of environmental factors such as heat and light. The physical and chemical properties of asphalt can be evaluated by measuring the penetration, softening point, bending strength, strain at break, asphalt composition, etc. In general, asphalt in which the maltene fraction in asphalt has migrated to asphaltene and the penetration has decreased is often called deteriorated asphalt. However, even if the penetration of recycled asphalt is the same as that of new asphalt, it may not be able to perform the same as new asphalt due to changes in other properties.

[0024] The asphalt mixture from which the used asphalt pavement is derived contains aggregate. Examples of such aggregate include aggregates commonly used in asphalt mixtures for road paving, such as crushed stone, boulders, gravel, sand, and ceramics. In addition, the asphalt mixture itself from which the used asphalt pavement is derived may use recycled asphalt aggregate as an aggregate.

[0025] [New aggregate] The asphalt mixture of the present invention can contain new aggregate in addition to recycled asphalt aggregate. The new aggregate is: Specific examples of aggregates that can be used include crushed stone, boulders, gravel, sand, ceramics, etc. Also, examples of aggregates that can be used include coarse aggregates with a particle size of 2.36 mm or more, fine aggregates with a particle size of 0.075 mm or more and less than 2.36 mm, and fillers with a particle size of less than 0.075 mm. Examples of coarse aggregate include crushed stone with a particle size range of 2.36 mm or more and less than 4.75 mm, crushed stone with a particle size range of 4.75 mm or more and less than 12.5 mm, crushed stone with a particle size range of 12.5 mm or more and less than 19 mm, and crushed stone with a particle size range of 19 mm or more and less than 31.5 mm. Examples of fine aggregates include river sand, dune sand, mountain sand, sea sand, crushed sand, fine sand, screenings, crushed stone dust, silica sand, artificial sand, glass cullet, and foundry sand. The particle size of coarse aggregate and fine aggregate is based on the sieve analysis test method specified in JIS A5001:2008.

[0026] Examples of the filler include sand, fly ash, calcium carbonate powder such as limestone powder, hydrated lime, etc. Among these, calcium carbonate powder is preferred from the viewpoint of improving the strength of the asphalt pavement. From the viewpoint of improving the strength of the asphalt pavement, the average particle size of the filler is preferably 0.001 mm or more, and preferably 0.05 mm or less, more preferably 0.03 mm or less, and further preferably 0.02 mm or less. Here, the average particle size is the average particle size at 50% cumulative volume (D 50 ) and can be measured using a laser diffraction particle size distribution analyzer.

[0027] As the aggregate, it is preferable to use a combination of coarse aggregate and fine aggregate. In this case, from the viewpoint of durability of the asphalt pavement, the mass ratio of the coarse aggregate to the fine aggregate (coarse aggregate / fine aggregate) is preferably 10 / 90 or more, more preferably 15 / 85 or more, even more preferably 20 / 80 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.

[0028] <Polyester resin> The asphalt mixture of the present invention may further comprise a polyester resin. The polyester resin is a polycondensation product of an alcohol component and a carboxylic acid component, and contains a structural unit derived from an alcohol component and a structural unit derived from a carboxylic acid component. The polyester resin may be an amorphous polyester resin or a crystalline polyester resin, and is preferably an amorphous polyester resin. The alcohol component and the carboxylic acid component will be described below.

[0029] (Alcohol content) Examples of the alcohol component include an aliphatic diol, an alicyclic diol, an aromatic diol, a trihydric or higher polyhydric alcohol, etc. These alcohol components may be used alone or in combination of two or more kinds.

[0030] The aliphatic diol is preferably a linear or branched aliphatic diol having 2 to 12 carbon atoms in the main chain, and more preferably a linear or branched aliphatic diol having 2 to 8 carbon atoms in the main chain. Also, the aliphatic diol is preferably a saturated aliphatic diol. Specific examples of aliphatic diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,10-decanediol, and 1,12-dodecanediol.

[0031] Examples of alicyclic diols include hydrogenated bisphenol A (2,2-bis(4-hydroxycyclohexyl)propane), alkylene oxide adducts of hydrogenated bisphenol A, cyclohexanediol, and cyclohexanedimethanol.

[0032] Examples of aromatic diols include bisphenol A (2,2-bis(4-hydroxyphenyl)propane) and alkylene oxide adducts of bisphenol A. Examples of alkylene oxide adducts of bisphenol A include alkylene oxide adducts of bisphenol A represented by the following formula (I).

[0033] [ka]

[0034] [In the formula, OR 1 and R 1 O is an alkylene oxide, and R 1is an alkylene group having 2 or 3 carbon atoms, x and y are positive numbers indicating the average number of moles of alkylene oxide added, and the sum of x and y is preferably 1 or more, more preferably 1.5 or more, and is preferably 16 or less, more preferably 8 or less, and even more preferably 4 or less.

[0035] Examples of the alkylene oxide adduct of bisphenol A represented by formula (I) include a propylene oxide adduct of bisphenol A and an ethylene oxide adduct of bisphenol A. These alkylene oxide adducts of bisphenol A can be used alone or in combination of two or more kinds.

[0036] The trihydric or higher polyhydric alcohol is preferably a trihydric alcohol, and examples of the trihydric or higher polyhydric alcohol include glycerin, pentaerythritol, trimethylolpropane, and sorbitol.

[0037] The alcohol component may further contain a monohydric aliphatic alcohol from the viewpoint of adjusting physical properties. Examples of the monohydric aliphatic alcohol include lauryl alcohol, myristyl alcohol, palmityl alcohol, and stearyl alcohol. These monohydric aliphatic alcohols may be used alone or in combination of two or more.

[0038] (Carboxylic acid component) Examples of the carboxylic acid component include aliphatic dicarboxylic acids, aromatic dicarboxylic acids, and polyvalent carboxylic acids having a valence of 3 to 6. These carboxylic acid components can be used alone or in combination of two or more.

[0039] Examples of the aliphatic dicarboxylic acid include aliphatic dicarboxylic acids having a main chain carbon number of preferably 4 or more and preferably 10 or less, more preferably 8 or less, and more preferably 6 or less, such as fumaric acid, maleic acid, oxalic acid, malonic acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms, or anhydrides thereof, and alkyl esters thereof (e.g., alkyl groups having 1 to 3 carbon atoms). Examples of the substituted succinic acid include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid.

[0040] Examples of aromatic dicarboxylic acids include phthalic acid, terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, anhydrides thereof, and alkyl esters thereof (for example, alkyl groups having 1 to 3 carbon atoms). Among the above aromatic dicarboxylic acids, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred, from the viewpoints of suppressing aggregate scattering and water resistance.

[0041] The polyvalent carboxylic acid having a valence of 3 to 6 is preferably a trivalent carboxylic acid. Examples of the polyvalent carboxylic acid having a valence of 3 to 6 include trimellitic acid, 2,5,7-naphthalenetricarboxylic acid, pyromellitic acid, and acid anhydrides thereof.

[0042] The carboxylic acid component may further contain a monovalent aliphatic carboxylic acid from the viewpoint of adjusting physical properties. Examples of the monovalent aliphatic carboxylic acid include monovalent aliphatic carboxylic acids having 12 to 20 carbon atoms, such as lauric acid, myristic acid, palmitic acid, stearic acid, and alkyl (having 1 to 3 carbon atoms) esters of these acids. These monovalent aliphatic carboxylic acids may be used alone or in combination of two or more kinds.

[0043] (Structural unit derived from polyethylene terephthalate) The polyester resin may contain ethylene glycol-derived structural units and terephthalic acid-derived structural units derived from polyethylene terephthalate. The polyethylene terephthalate may contain small amounts of components such as butanediol and isophthalic acid in addition to the structural units derived from ethylene glycol and terephthalic acid. The polyethylene terephthalate is preferably recycled polyethylene terephthalate. When the polyester resin contains structural units consisting of ethylene glycol and terephthalic acid derived from polyethylene terephthalate, the "structural units derived from an alcohol component" contain structural units derived from ethylene glycol derived from polyethylene terephthalate, and the "structural units derived from a carboxylic acid component" contain structural units derived from terephthalic acid derived from polyethylene terephthalate.

[0044] The polyester resin may be modified to such an extent that its properties are not substantially impaired.Specific examples of the modified polyester resin include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc.Preferred modified polyester resins include urethane-modified polyester resins obtained by urethane-extending polyester resins with a polyisocyanate compound.

[0045] <Content of each ingredient> From the viewpoint of achieving both durability and flexibility, the asphalt content in the asphalt mixture is preferably 1 mass% or more, more preferably 3 mass% or more, even more preferably 4 mass% or more, and preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less.

[0046] In the present invention, the asphalt content is the total content of new asphalt and asphalt contained in recycled asphalt aggregate. In the present invention, the asphalt contained in recycled asphalt aggregate is also called asphalt derived from recycled aggregate to distinguish it from new asphalt. Asphalt derived from recycled aggregate is sometimes called deteriorated asphalt. From the viewpoint of achieving both durability and flexibility, the content of the new asphalt in the asphalt is preferably 50% by mass or more, more preferably 60% by mass or more, and preferably 80% by mass or less, and more preferably 70% by mass or less. From the viewpoint of achieving both durability and flexibility, the content of the asphalt derived from recycled aggregate in the asphalt is preferably 20% by mass or more, more preferably 30% by mass or more, and preferably 50% by mass or less, and more preferably 40% by mass or less. The content of asphalt derived from recycled aggregate in recycled asphalt aggregate can be measured by solvent extraction method or ignition loss method. Usually, the content of asphalt contained in recycled asphalt aggregate derived from used asphalt pavement is about 5.5 mass%. In the present invention, the content of asphalt derived from recycled aggregate is measured according to the method specified in AASHTO (American Association of State Highway and Transportation Officials) T 308-10 (2015), which is a loss on ignition measurement. Since recycled asphalt aggregate is included as an aggregate, the amount of asphalt is calculated from the loss on ignition of the recycled asphalt aggregate and used in the mix calculation.

[0047] The content of the polymer metal salt (P) in the asphalt mixture of the present invention is preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more, per 100 parts by mass of the total amount of new asphalt and asphalt derived from recycled aggregate, from the viewpoint of improving the durability of the asphalt pavement, and from the viewpoint of maintaining workability, it is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 7 parts by mass or less.

[0048] From the same viewpoint, the content of the polymer metal salt (P) in the asphalt mixture is preferably 2 parts by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more, per 100 parts by mass of asphalt derived from recycled aggregate, and from the viewpoint of maintaining workability, it is preferably 60 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 25 parts by mass or less, and even more preferably 12 parts by mass or less.

[0049] From the viewpoint of achieving both durability and flexibility, the aggregate content in the asphalt mixture is preferably 50% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, and preferably 99% by mass or less, more preferably 98% by mass or less, even more preferably 96% by mass or less. The content of recycled asphalt aggregate in the asphalt mixture is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, from the viewpoint of reusing waste asphalt pavement materials, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less, from the viewpoint of achieving both durability and flexibility.

[0050] In the present invention, the aggregate content is the total content of recycled asphalt aggregate and optionally contained new aggregate. The aggregate content includes the content of asphalt derived from recycled aggregate. When the aggregate contains new aggregate, the content of the new aggregate is preferably 40 parts by mass or more, more preferably 50 parts by mass or more, and preferably 80 parts by mass or less, more preferably 75 parts by mass or less, per 100 parts by mass of the total content of the asphalt recycled aggregate and the new aggregate, from the viewpoint of reusing waste materials from asphalt pavement, and is preferably 15 parts by mass or more, more preferably 25 parts by mass or more, per 100 parts by mass of the total content of the asphalt recycled aggregate and the new aggregate, from the viewpoint of reusing waste materials from asphalt pavement, and is preferably 60 parts by mass or less, more preferably 50 parts by mass or less, from the viewpoint of reusing waste materials from asphalt pavement.

[0051] Examples of suitable aggregate blends for asphalt mixtures include the following (1) to (3): (1) Fine-graded asphalt containing 30% to less than 45% by volume of coarse aggregate, 30% to less than 50% by volume of fine aggregate, and 5% to less than 10% by volume of asphalt composition. (2) An example of an asphalt mixture is dense-graded asphalt containing 45% to less than 70% by volume of coarse aggregate, 20% to 45% by volume of fine aggregate, and 3% to 10% by volume of asphalt composition. (3) Porous asphalt containing 70% to 80% by volume of coarse aggregate, 10% to 20% by volume of fine aggregate, and 3% to 10% by volume of asphalt composition. The mixing ratio of asphalt in conventional asphalt mixtures containing aggregate and asphalt is usually determined according to the optimal amount of asphalt obtained from the "Mix Design of Asphalt Composition" described in the "Guidelines for Pavement Design and Construction" issued by the Japan Road Association, a public interest incorporated association. In the present invention, the above-mentioned optimum amount of asphalt corresponds to the total amount of asphalt and polymer metal salt (P). However, it is not necessary to be limited to the method described in the "Guidelines for Pavement Design and Construction" and it may be determined by other methods.

[0052] In general, asphalt mixtures containing recycled asphalt aggregates can contain oils such as petroleum lubricant-based regeneration additives, animal and vegetable oil-based or petroleum-based workability improvers, etc., in order to soften the asphalt derived from the recycled aggregates and improve its flexibility. Specifically, the oils include petroleum and mineral oils, hydrocarbons similar thereto, and additives such as animal and vegetable oils and fats similar thereto. On the other hand, the asphalt mixture of the present invention preferably does not contain oil from the viewpoint of suppressing a decrease in durability. When the asphalt mixture of the present invention contains oil, the content thereof is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of asphalt derived from recycled aggregate, from the viewpoint of suppressing durability. In addition, when the oil is contained, the content thereof is preferably less than the content of the polymer metal salt (P).

[0053] [Asphalt mixture manufacturing method] The method for producing an asphalt mixture of the present invention includes a step of mixing a novel asphalt, a polymer metal salt (P), and an asphalt recycled aggregate under heating conditions. In the mixing step, new asphalt, polymer metal salt (P), and recycled asphalt aggregate can be mixed simultaneously or in any order. From the viewpoint of durability and flexibility of the asphalt pavement, preferably, the polymer metal salt (P) is mixed with the recycled asphalt aggregate simultaneously with or after the new asphalt. Mixing under heated conditions is preferably carried out in an embodiment using heated recycled asphalt aggregate. When the asphalt mixture contains new aggregate in addition to recycled asphalt aggregate, the recycled asphalt aggregate and the new aggregate can be mixed and used, for example, so as to achieve the above-mentioned content. Specific methods for producing asphalt mixtures include conventional methods for producing asphalt mixtures called the plant mix method and the premix method. Both are methods in which new asphalt and polymer metal salt (P) are added to heated aggregate. Examples of the addition method include the premix method in which new asphalt and polymer metal salt (P) are dissolved in advance, and the plant mix method in which new asphalt is added to heated aggregate and then the polymer metal salt (P) is added simultaneously or in random order. Among these, the plant mix method is preferred from the viewpoint of exerting asphalt performance. More specifically, in the method for producing an asphalt mixture, in the mixing step, preferably, (i) Adding and mixing new asphalt to heated aggregate to obtain a mixture, and then adding and mixing the polymer metal salt (P); (ii) Add and mix the new asphalt and the polymer metal salt (P) simultaneously to the heated aggregate; or (iii) A mixture of the pre-heated and mixed new asphalt and the above polymer metal salt (P) is added to and mixed with the heated aggregate. Among these, the mixing step is preferably the method (i). That is, the step of mixing under the heating conditions preferably includes a step of mixing the new asphalt with the recycled asphalt aggregate to obtain a mixture X, and a step of mixing the mixture X with the polymer metal salt (P).

[0054] The heating temperature is preferably 160° C. or higher, more preferably 165° C. or higher, and even more preferably 170° C. or higher, from the viewpoint of improving durability by sufficient mixing, and is preferably 350° C. or lower, more preferably 250° C. or lower, and even more preferably 200° C. or lower, from the viewpoint of performance stability. Furthermore, from the viewpoint of efficiently dispersing the polymer metal salt (P) uniformly in the asphalt and exerting the asphalt performance, the mixing time is preferably 0.1 hour or more, more preferably 0.5 hour or more, even more preferably 1.0 hour or more, even more preferably 1.5 hour or more, and is preferably 10 hours or less, more preferably 7 hours or less, even more preferably 5 hours or less, even more preferably 3 hours or less.

[0055] The method for preparing the mixture is not particularly limited, but it is preferable to include a process of heating and melting the novel asphalt, adding the polymer metal salt (P) and other additives as necessary, and stirring and mixing the components in a commonly used mixer until they are uniformly dispersed. Commonly used mixers include homomixers, dissolvers, paddle mixers, ribbon mixers, screw mixers, planetary mixers, vacuum countercurrent mixers, roll mills, twin-screw extruders, etc.

[0056] The asphalt mixture of the present invention may be used as a heated asphalt mixture substantially free of water, or may be used as a cold asphalt mixture by blending an emulsifier and water into the asphalt mixture to form an asphalt emulsion, which may then be blended with aggregates and the like. From the viewpoint of exerting asphalt performance, the mixture of asphalt, polyester resin, and the polymer metal salt (P) preferably does not substantially contain water.

[0057] In a method for producing an asphalt mixture using recycled asphalt aggregate, a technique is known in which oils such as petroleum lubricant-based regeneration additives, animal and vegetable oil-based or petroleum-based workability improvers, etc. are added to soften the asphalt derived from the recycled aggregate and improve its flexibility, and then cured. Specifically, examples of oils include petroleum oil, mineral oil, and similar hydrocarbons, or animal oil, vegetable oil, and similar oils and fats. On the other hand, in the method for producing an asphalt mixture of the present invention, excellent flexibility and durability can be achieved without carrying out such treatment. Therefore, in the method for producing an asphalt mixture of the present invention, preferably, oil is not added before the step of mixing the novel asphalt, the polymer metal salt (P), and the recycled asphalt aggregate under heating conditions. In other words, it is preferable to use the recycled asphalt aggregate without any processing other than crushing and classification. The step of mixing under heating conditions is a step of mixing only the novel asphalt, the j polymer metal salt (P), the recycled asphalt aggregate, and optionally one or more selected from the group consisting of polymers such as polyester resins and additives other than the recycling additives and the workability improving agents.

[0058] When the asphalt mixture is used as a heated asphalt mixture, there are no particular limitations on the method for producing the asphalt mixture, and the asphalt mixture may be produced by any method. Generally, the method may be similar to the method for producing an asphalt mixture containing aggregate and an asphalt composition.

[0059] [Road pavement construction method] The asphalt mixture of the present invention is suitable for road pavement. The road pavement construction method of the present invention preferably includes a step of applying the asphalt mixture of the present invention to a road or the like to form an asphalt pavement layer. The asphalt pavement layer is usually the base layer or surface layer of a road, and is preferably the surface layer of a road from the viewpoint of exerting the effect of durability.

[0060] In the road paving method, the asphalt mixture may be compacted and constructed using the same construction machinery and method as for normal asphalt mixtures. The compaction temperature of the asphalt mixture when used as a heated asphalt mixture is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher, from the viewpoint of exerting asphalt performance, and is preferably 200°C or lower, more preferably 180°C or lower, and even more preferably 170°C or lower. EXAMPLES

[0061] Various physical properties were measured and evaluated by the following methods. In the following examples and comparative examples, parts and percentages are by weight unless otherwise specified.

[0062] Example 1 15 kg of aggregate containing recycled asphalt aggregate heated to 180°C (see below for the composition of the aggregate) was placed in an asphalt mixer and mixed at 180°C for 60 seconds. Next, 520 g of straight asphalt (manufactured by Mitsubishi Corporation Energy Co., Ltd.) was added and mixed for 1 minute in the asphalt mixer. Next, 24 g of polymer metal salt P-1 (Demoll MS (trade name), manufactured by Kao Corporation, sodium salt of methylnaphthalenesulfonic acid formalin condensate) was added and mixed for 2 minutes in the asphalt mixer to obtain an asphalt mixture. <Aggregate composition> No. 6 crushed stone 28.0 parts by weight No. 7 crushed stone 9.0 parts by weight Crushed sand 7.0 parts by mass River sand 16.0 parts by mass Mountain sand 7.0 parts by mass Stone powder (calcium carbonate) 3.0 parts by weight Recycled asphalt aggregate 30.0 parts by mass Passed mass%: Sieve size 15 mm: 100% by mass Sieve size 10 mm: 84.4% by mass Sieve size 5 mm: 61.7% by mass Sieve size 2.5 mm: 43.9% by mass Sieve size 1.2 mm: 30.8% by mass Sieve size 0.6 mm: 19.0% by mass Sieve size 0.3 mm: 10.6% by mass Sieve size 0.15mm: 4.7% by mass

[0063] The content of asphalt derived from recycled aggregate in the asphalt recycled aggregate was 269g. The total content of new asphalt and asphalt derived from recycled aggregate was 789g, and the content of asphalt in the asphalt mixture (total amount of new asphalt and asphalt derived from recycled aggregate) was 5% by mass. In Table 1, it is shown as "Content (1)". The content of polymer metal salt P-1 was 9 parts by mass per 100 parts by mass of asphalt derived from recycled aggregate, and 3 parts by mass per 100 parts by mass of the total amount of asphalt. The asphalt content of recycled asphalt aggregate was estimated according to the method specified in AASHTO T 308-10 (2015). In Table 1, this is shown as “content (2).”

[0064] [evaluation] <Marshall stability test> 1.2 kg of the resulting asphalt mixture was weighed out and stored at 180°C for 2 hours for thermal curing. It was then compacted using a Marshall test compactor "Automatic Asphalt Compaction Device" (manufactured by Nakajima Gihan Co., Ltd.) 50 times on each side for a total of 100 times to produce cylindrical asphalt specimen M-1. The demolded asphalt specimen M-1 was immersed in a 60°C thermostatic water tank for 30 minutes, and then the overturned asphalt specimen M-1 was crushed with a flat plate at a speed of 50 mm / min using a Marshall loading device (manufactured by Nakajima Gihan Co., Ltd.). The maximum load shown until destruction was recorded as the Marshall stability. In addition, the amount of displacement from the start of the displacement slope to the maximum load was measured and recorded as the flow value. Other measurement conditions were in accordance with the "B001 Marshall Stability Test" described in the "Pavement Survey and Test Method Handbook" published by the Japan Road Association. The higher the Marshall stability value, the more durable the asphalt pavement is. The flow value is used as an index of flexibility at the service temperature of the asphalt pavement. The results are shown in Table 1.

[0065] Examples 2 to 9, Comparative Examples 1 to 4 Except for changing the composition of the asphalt mixture to that shown in Table 1, asphalt specimens were prepared in the same manner as in Example 1, and Marshall stability tests were performed to measure the Marshall stability and flow value. The other components shown in Table 1 were added at the same time that the polymer metal salt P-1 of Example 1 was added. The results are shown in Table 1.

[0066] The polymer metal salts used in Examples 1 to 9 and the polymers used in Comparative Examples 2 to 4 are shown below. Polymer metal salt P-1: Demol MS (trade name), manufactured by Kao Corporation, sodium salt of methylnaphthalenesulfonic acid formalin condensate Polymer metal salt P-2: Demol SN-B (product name), manufactured by Kao Corporation, sodium salt of butylnaphthalene / naphthalenesulfonic acid formalin condensate Polymer metal salt P-3: Mighty 100 (product name), manufactured by Kao Corporation, sodium salt of naphthalenesulfonic acid formalin condensate, high molecular weight type Polymer metal salt P-4: Demol N (trade name), manufactured by Kao Corporation, sodium salt of β-naphthalenesulfonic acid formalin condensate Polymer metal salt P-5: Polystyrene sulfonate sodium salt, reagent (Alfa Aesar) Weight average molecular weight 70,000

[0067] Polymer p-1: Unneutralized naphthalenesulfonic acid formalin condensate Polymer p-1 was obtained by the following production method. 1.28 mol of 98% sulfuric acid was added to 1 mol of naphthalene, and the sulfonation reaction was carried out for 3 hours at a reaction temperature of 155° C. to 160° C. Then, 0.97 mol of formaldehyde (35% formalin) was added, and the condensation reaction was completed at a reaction temperature of 100° C. for 12 hours to obtain a naphthalenesulfonic acid formalin condensate. The polymer p-1 corresponds to the unneutralized product of the polymer metal salt P-3.

[0068] Polymer p-2: Neopelec GS (product name), manufactured by Kao Corporation, alkylbenzene sulfonic acid

[0069] Polyester q-1: Polyester q-1 was prepared by the following method. 3943g (molar ratio 40) of polyoxypropylene (2.2 moles) adduct of bisphenol A, 1103g (molar ratio 83.6) of terephthalic acid, and 3244g (molar ratio 60 moles as ethylene glycol) of PET (polyethylene terephthalate, manufactured by Indorama Ventures) were placed in a 10L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a downflow condenser, and a nitrogen inlet tube, and 45g of di(2-ethylhexanoate) tin(II) was added in a nitrogen atmosphere, and the temperature was raised to 235°C over 3 hours in a mantle heater, and the temperature was maintained at 235°C for 5 hours, after which a reduced pressure reaction was carried out at 8.0 kPa for 1 hour. After visually confirming that the PET particles had disappeared from the reaction product, the reaction product was cooled to 180°C, and 710g (molar ratio 9.4) of alkenyl succinic anhydride was added. After heating up to 210°C over 2 hours, the mixture was kept at 210°C for 1 hour and reacted under reduced pressure at 8.3 kPa. The reaction was continued until the softening point reached 105.2°C to obtain polyester q-1.

[0070] [Table 1]

[0071] The results shown in Table 1 show that the present invention uses recycled asphalt aggregate and provides an asphalt mixture that can provide an asphalt pavement that is excellent in durability and flexibility. Furthermore, when Example 9 is compared with Comparative Example 3, it is found that even when the polyester q-1 is further contained, an asphalt mixture capable of providing an asphalt pavement having excellent durability and flexibility can be obtained.

[0072] Reference examples 1~2 In Reference Example 1, an asphalt specimen was prepared in the same manner as in Comparative Example 1, except that the aggregate containing recycled asphalt aggregate was changed to an aggregate not containing recycled asphalt aggregate (see below for the composition of the aggregate), and a Marshall stability test was performed to measure the Marshall stability and flow value. In Reference Example 2, an asphalt specimen was prepared in the same manner as in Example 1, except that the aggregate containing recycled asphalt aggregate was changed to an aggregate not containing recycled asphalt aggregate, and a Marshall stability test was performed to measure the Marshall stability and flow value. The results are shown in Table 2. <Aggregate not including recycled asphalt aggregate> Aggregate composition: No. 6 crushed stone 40.0 parts by weight No. 7 crushed stone 13.0 parts by weight Crushed sand 10.0 parts by mass River sand 22.0 parts by mass Mountain sand 10.0 parts by mass Stone powder (calcium carbonate) 5.0 parts by weight Passed mass%: Sieve size 15 mm: 100% by mass Sieve size 10 mm: 88.7% by mass Sieve size 5 mm: 60.5% by mass Sieve size 2.5 mm: 42.6% by mass Sieve size 1.2 mm: 29.9% by mass Sieve size 0.6 mm: 19.8% by mass Sieve size 0.3 mm: 11.5% by mass Sieve size 0.15mm: 6.2% by mass

[0073] [Table 2]

[0074] The results shown in Table 2 show that when the asphalt mixture does not contain recycled asphalt aggregate, there is no significant difference in durability and flexibility even when a polymer metal salt is added.

Claims

1. An asphalt mixture containing a new asphalt, the following polymer metal salt (P), and recycled asphalt aggregate. Polymer metal salt (P): a metal salt of a polymer having a structural unit derived from an aromatic monomer and having an acidic group in the structural unit.

2. 2. The asphalt mixture of claim 1, wherein the acidic groups are sulfonic acid groups.

3. The asphalt mixture according to claim 1 or 2, wherein the aromatic monomer is an aromatic monomer having an aromatic ring skeleton in its main chain.

4. 3. The asphalt mixture according to claim 1 or 2, wherein the polymer is a polymer obtained by a condensation polymerization process.

5. The asphalt mixture according to claim 1 or 2, wherein the aromatic monomer is an aromatic monomer having a naphthalene skeleton.

6. 3. The asphalt mixture according to claim 1 or 2, wherein the novel asphalt is a straight asphalt or a modified asphalt.

7. The asphalt mixture of claim 1 or 2, wherein the asphalt mixture further comprises a polyester resin.

8. The content of the polymer metal salt (P) is 1 part by mass or more and 15 parts by mass or less per 100 parts by mass of the total amount of the new asphalt and the asphalt derived from the recycled aggregate. The asphalt mixture according to claim 1 or 2.

9. The asphalt mixture according to claim 1 or 2, wherein the content of the polymer metal salt (P) is 2 parts by mass or more and 60 parts by mass or less per 100 parts by mass of the total amount of asphalt derived from the recycled aggregate.

10. A method for producing an asphalt mixture, comprising a step of mixing a new asphalt, the following polymer metal salt (P), and recycled asphalt aggregate under heating conditions. Polymer metal salt (P): a metal salt of a polymer having a structural unit derived from an aromatic monomer and having an acidic group in the structural unit.

11. The method for producing an asphalt mixture according to claim 10, wherein no oil is added before the step of mixing the new asphalt, the polymer metal salt (P), and the asphalt recycled aggregate under heating conditions.

12. The method for producing an asphalt mixture according to claim 10 or 11, wherein the heating temperature for mixing is 160°C or higher and 350°C or lower.

13. The step of mixing under heating conditions includes a step of mixing the new asphalt and the recycled asphalt aggregate to obtain a mixture X, and a step of mixing the mixture X and the polymer metal salt (P). The method for producing an asphalt mixture according to claim 10 or 11.

14. The content of the polymer metal salt (P) in the asphalt mixture is 1 part by mass or more and 15 parts by mass or less per 100 parts by mass of the total amount of the new asphalt and the asphalt derived from the recycled aggregate. The method for producing an asphalt mixture according to claim 10 or 11.

15. The content of the polymer metal salt (P) in the asphalt mixture is 2 parts by mass or more and 60 parts by mass or less per 100 parts by mass of the total amount of asphalt derived from the recycled aggregate. The method for producing an asphalt mixture according to claim 10 or 11.

16. A road paving method, comprising a step of applying the asphalt mixture according to claim 1 or 2 to a road to form an asphalt pavement layer.

17. The road paving method according to claim 16, comprising compaction work, the compaction temperature of the asphalt mixture being 100°C or higher and 200°C or lower.

Citation Information

Patent Citations

  • Environment-friendly special emulsified asphalt for dust suppression of road surface, and preparation method and construction method of environment-friendly special emulsified asphalt

    CN111944323A

  • Aggregate for asphalt emulsion

    JP1997012896A

  • Method for regenerating aggregate from destruction rubbish of asphalt

    JP1998057834A

  • Asphalt emulsion for slow set

    JP2000169719A

  • Rubber asphalt composition

    JP2017206634A